Pengaruh Motivasi, Pengembangan Karir, Dan Lingkungan Kerja Terhadap Kinerja Karyawan Di PT. Ekadharma International Tbk - Ajeng Kusuma Ningsih; Parwita Setya Wardhani; Tri Wahjoedi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the influence of work motivation, career development, and work environment on employee performance at PT. Ekadharma International TBK. The population studied in this study is work motivation, career development, and work environment have a positive and significant influence on employee performance. The number of samples in this study was carried out by probability sampling. The data collection technique used in this study is a questionnaire used in the study is a questionnaire distributed to all employees at PT. EKADHARMA INTERNATIONAL TBK. The data analysis technique used in this study is multiple linear regression analysis using SPSS (Statistic Product and Services Solution) software version 29.0. The results of the study indicate that the motivation variable has a positive and significant effect on employee performance with a t-count value = 4.614 > t-table 2.012, the career development variable has a positive and significant effect on employee performance with a t-count value = 3.081 > t-table 2.012, the work environment variable has a positive and significant effect on employee performance with a t-count value = 3.238 > t-table 2012. From the three results, it shows that motivation, career development and work environment have a partial effect on employee performance. For joint testing, they have a significant effect on employee performance.